Judicial Progress in Germany's Nuclear Waste Disposal Policy, The Konrad Repository Decisions of 26 March 2007 - Kühne, Gunther (OECD Publishing, 2012)
The installation of final repositories for nuclear waste has been a most controversial topic on the German political agenda for decades. The beginning of efforts to solve this problem can be traced back to the 1970s when plans for the establishment of an Integrated Nuclear Waste Disposal Centre (Integriertes Entsorgungszentrum) in the State of Lower Saxony were developed. It was in this context that in 1976,1 the Atomic Energy Act (AEA) of 19592 (the 2002 consolidated text is reproduced in Supplement to Nuclear Law Bulletin No. 70) was amended by inserting Section 9a, paragraph 3, sentence 1, which reads very succinctly: "The Federation shall establish installations for the safekeeping and final disposal of radioactive waste." Despite the subsequent AEA amendments of Section 9a, paragraph 3 and the addition of a paragraph 4 (1998)3 that were to allow the Federation to transfer the exercise of its functions to third parties, these administrative provisions were never used. Accordingly, full responsibility of the Federation for the fulfilment of its obligation under Section 9a, paragraph 3 of the AEA remains intact today
Keywords: Nuclear Energy; Germany